Glucocorticoid Receptor-β is Downregulated by Vitamin D Treatment in Children with Low Vitamin D Levels but Not in Allergic Asthma - ÖZEN, AHMET OĞUZHAN (Mary Ann Liebert Inc., 2015)
Background: Vitamin D (VitD) enhances the anti-inflammatory effects of glucocorticoids (GC) in vitro. It was hypothesized that VitD3 (colecalciferol) treatment could have an impact on the expression of glucocorticoid receptors (GRs) in a group of children with low VitD levels, with or without asthma. Methods: Asthmatic children and healthy controls, all with low serum VitD levels (25-hydroxyvitamin D [25(OH)D] level <30ng/mL) were recruited. VitD3 treatment at a dose of 300,000IU was given orally. Blood samples were obtained at admission and 1 month after the treatment to examine serum 25(OH)D levels and the relative gene expression (RGE) of GR-α and -β in peripheral blood mononuclear cells. Results: Twenty-four children with asthma (Mage 11.1±2.1 years) and 14 healthy controls (Mage 11.5±1.7 years) were studied. The expression of GR-β was significantly higher in the control group at baseline compared with those with asthma (p=0.006). With VitD3 treatment, there was a decrease in GRβ expression at 1 month in the control group (p=0.05), but not in the asthma group. When analyzing the change in the relative expression of GRβ (change in 1st month to baseline), the decrease in GRβ was significantly higher in the control group compared with the asthma group (p=0.002). A negative correlation was detected between the change in the asthma control test score (ACT) and the change in 25(OH)D values (r=-0.51, p=0.01). Conclusion: VitD3 supplementation led to a decrease in the expression of GRβ in control subjects with low baseline VitD levels, whereas no such change was observed in asthmatic children. Meanwhile, better asthma control was achieved by VitD3 treatment, possibly through mechanisms not related to GR expression. © Copyright 2015, Mary Ann Liebert, Inc. 2015.